Controller and anti‐windup co‐design for the output regulation of rational systems subject to control saturation - Castro, Rafael S.; Flores, Jeferson V.; Salton, Aurélio T.; Gomes da Silva Jr, João M (International journal of robust and nonlinear control, 2021)
This article presents a novel framework for the output regulation of rational nonlinear systems subject to input saturation, where the controller structure is composed by an internal model generator in series with an output feedback stabilizing stage. In order to address the effects of control saturation, we propose the use of an anti‐windup compensation loop into both internal model and stabilizing control stages. Given prior knowledge of the system zero‐error steady‐state condition and a proper internal model, we cast the regulation error dynamics in a differential‐algebraic form, which leads to matrix inequalities conditions that ensure closed‐loop stability and exponential transient performance. Optimization problems are then proposed to simultaneously compute the stabilizing controller and the anti‐windup gains such that a domain of attraction estimate is maximized.